1976
DOI: 10.1111/j.1365-2621.1976.tb00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Oligosaccharides During Cooking of Whole Soybeans

Abstract: Raffinose and stachyose present in soybeans have been reported to cause flatulence. The objective of this work was to study the aqueous extraction of whole soybeans during water cooking to determine optimum conditions for maximum removal of oligosaccharides with minimum loss of protein. Chief variables were bean to water ratio (1:3, 1:5, 1:7.5 and 1: 10) and pH. Residual oligosaccharides in the soybeans were determined by silylation followed by GLC analysis. During 20 min boiling in water, a 1:lO ratio resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Information on the amounts of oligosaccharides extracted from soybean seeds during cooking has been reported by Ku et al (1976). The traditional method for home preparation of this leguminous seed consists of a water soaking period (usually overnight) followed by cooking of the dehydrated seeds after discarding the soaking water.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the amounts of oligosaccharides extracted from soybean seeds during cooking has been reported by Ku et al (1976). The traditional method for home preparation of this leguminous seed consists of a water soaking period (usually overnight) followed by cooking of the dehydrated seeds after discarding the soaking water.…”
Section: Introductionmentioning
confidence: 99%
“…This may be likely due to an increase in the sodium content as a result of the sodium bicarbonate pre-processing of the beans. This has been reported previously for soymilk [8,22]. The proximate composition of the morama milk samples was however significantly different to that of soymilk.…”
Section: Volume 13 No 1 January 2013mentioning
confidence: 57%
“…Previous studies on processing of soymilk also reported on changes in the protein and carbohydrate content [8,22]. Protein changes were reported to occur between heated and unheated samples as well as those blanched in bicarbonate soda.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations